Expectations for therapy in pediatric rehabilitation: reframing meaning through metaphor. Issue 23 (6th November 2022) - Smart, Eric; Nalder, Emily; Trentham, Barry; King, Gillian
Abstract: Purpose: To propose a holistic approach and an accompanying tool to facilitate conversations about expectations of therapy in pediatric rehabilitation based on meanings generated through metaphor. Methods: In this study, five parents and nine service providers took part in narrative interviews. Topics included the content and development of expectations over time. Participants reviewed written summaries of their interviews and provided feedback. Data analysis was grounded in a narrative methodological approach. Multiple levels of meaning from participant experiences were constructed through a parallel thematic analysis and metaphor analysis, revealing meaning participants attributed to expectations directly, and inferred indirectly. Results: The thematic analysis produced three themes related to the difficult to define characteristics and mixed value of expectations. The metaphor analysis produced four metaphorical concepts related to how expectations affect the therapy process by adding a sense of Force (i.e., therapy momentum), Appreciation (i.e., understanding of the client), Illumination (i.e., envisioning new therapy activities), and Relationship (i.e., therapeutic rapport). Conclusions: We propose the "F.A.I.R." approach and tool comprising terminology that can help reframe the meaning of expectations away from focusing on binary realistic or unrealistic outcomes, and toward focusing on a plurality of optimal therapy processes. Implications for Rehabilitation: Meaningful conversations about expectations for therapy between parents and service providers in pediatric rehabilitation can be challenging, one-sided, or missed. Attention to metaphors used to describe expectations for therapy introduces additional terminology parents and service providers may use to help facilitate conversations. Service providers are encouraged to use a resource proposed here to learn about parents' expectations for therapy through a collaborative process involving shared questioning, observation, and reflection.